The role of Ubuntu in families living with mental illness in the community - C. Engelbrecht; M.I. Kasiram (South African Family Practice)
Background: Families living with mental illness are a vulnerable group in the community. In the African culture, it is accepted that families are embedded safely in a community. In accordance with the principles of Ubuntu, people with mental illness should be well supported and cared for by their families and the wider community. Traditionally, people with mental illness are institutionalised, out of sight of the family and the general population. However, the deinstitutionalisation of mental health services has changed the structure and mode of caring for people with mental illness. The family and community are now regarded as the dominant care givers and providers.